PENINGKATAN KINERJA INSEMINATOR DALAM PENGEMBANGAN BUDIDAYA PETERNAKAN ERA OTONOMI DAERAH - Didik Kusumahadi; Firman Jaya (Universitas Tribhuwana Tunggadewi, 2009)
Animal husbandry sector development plays an important role in fulfil the food from animal requirements by increase production continually to regional or national fulfilment in stamina of the food and economiy. Various effort and increase production by improvement and development program, create oppertunities for exertion, which have an impact to increase peoples income. It need human resource development is the most important for all activities like wise in animal husbandry sector. Improvment of human resourses competence expected to increase effectiveness and efficiency other resources that achieve the high productivity correlation with demand for global development, economic pressure result in situation change, technology and information development. It problem surmountable by develop learning organization. Animal Husbandry Service by husbandry sector development Nganjuk regency tried to create intitution as learning organization that intend to upgrade it role by implementation of accountable goverment of public administration. This effort can created by increase appararatus of Animal Husbandry Service competence that have rela tion with public service. It expected that have good governance to be carry out with can apply the principles of transpiration, participation, law supreme and public accountable. This result based SWOT analysis can be find out desicive factor (1). Husbandry commodity development by artificial insemination program that condusif public policy support, (2). Create condusif investation set the tone for husbandry sector, (3). Artificial insemination center has development as production regional by business partner system to realize income and prosperity of village communities, (4). Apply benefit technology to artificial insemination development in husbandry sector.